2014
DOI: 10.3390/w6113433
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Performance between Genetic Algorithm and SCE-UA for Calibration of SCS-CN Surface Runoff Simulation

Abstract: Global optimization methods linked with simulation models are widely used for automated calibration and serve as useful tools for searching for cost-effective alternatives for environmental management. A genetic algorithm (GA) and shuffled complex evolution (SCE-UA) algorithm were linked with the Long-Term Hydrologic Impact Assessment (L-THIA) model, which employs the curve number (SCS-CN) method. The performance of the two optimization methods was compared by automatically calibrating L-THIA for monthly runof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…From Arsenault et al (2014) one may learn that some algorithms initially converge quicker than the others, but such methods often perform worse than the best ones at the end of the search. A similar result was obtained by Jeon et al (2014), but for another goal, namely calibration of long-term hydrologic impact assessment model. On the contrary, although in Tolson and Shoemaker (2007) and Piotrowski et al (2017a) also differences in convergence speed between various algorithms applied for calibration of conceptual rainfall-runoff models are noted, finally vast majority of methods reach almost equal performance.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…From Arsenault et al (2014) one may learn that some algorithms initially converge quicker than the others, but such methods often perform worse than the best ones at the end of the search. A similar result was obtained by Jeon et al (2014), but for another goal, namely calibration of long-term hydrologic impact assessment model. On the contrary, although in Tolson and Shoemaker (2007) and Piotrowski et al (2017a) also differences in convergence speed between various algorithms applied for calibration of conceptual rainfall-runoff models are noted, finally vast majority of methods reach almost equal performance.…”
Section: Introductionsupporting
confidence: 63%
“…Would such results be similar to those obtained when different maximum numbers of function calls are assumed? For example, when setting the maximum number of function calls to 20,000, Jeon et al (2014) found that the variant of Genetic Algorithm they apply perform better than SCE-UA method (Duan et al 1992) until 5150 function evaluations is used, but SCE-UA is better afterwards. Does it means that when one sets the maximum number of function calls to 5000, Genetic Algorithm would still perform better?…”
Section: Introductionmentioning
confidence: 99%
“…Iskra and Droste [14] found that the random multiple search method (RSM) and the Shuffled Complex Evolution method (SCE-UA) could find a parameter set providing better model performance statistics than with PEST employing the GLM algorithm. Sahoo et al [4] calibrated the hydrologic components of HSPF using a generic algorithm (GA), but it has been suggested that the GA required greater computing resources and time for parameter calibration than SCE-UA, making running the model less efficient [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The idea of complex shape segmentation and mixing introduced in this algorithm improves search efficiency, computation speed, and global search ability. SCE-UA is not sensitive to the initial values of the optimization parameters, thus avoiding excessive reliance on prior knowledge during optimization process and solves the problems caused by missing initial parameter values [35]. Research shows that SCE-UA can converge to the global optimal solution efficiently due to its fast convergence speed and good stability [36].…”
Section: The Sce-ua Algorithmmentioning
confidence: 99%